Comprehension and production in hearing impaired children - K, Seena (Journal of All India Institute of Speech and Hearing)
Contradicting the commonly held view, two Indian studies reported language expression to be better than language reception. In this context, the present study was taken up and it aimed at finding the nature of relationship between comprehension and expression in hearing impaired children within a particular age group and across different age groups.